Terror laktacyjny w przestrzeni wirtualnej - Marcinkiewicz, Aleksandra (Wydział Studiów Edukacyjnych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The aim of paper is to show problem of putting social pressure on mothers to breastfeeding. The internet forum about terror lactation was analyzed. In research used qualitative analyses of context. The results of study had shown the ratio of mothers to breastfeed, forms of pressure on mothers and social groups which put this pressure. It was shown stereotypes which exist in virtual space about women and breastfeeding.
Lactational Terror in Virtual Space
Keywords: lactational terror; motherhood; social pressure; woman